Impact and Usage of Social Media in Business Sector during Covid-19 Pandemic - Dhanshri Suresh Yadav; Manisha V Jagtap (Universitas Komputer Indonesia, 2022)
The Impact of covid-19 faced by whole world. The economic growth of all the countries is going down because of covid-19. In India, the covid-19 affected all the sectors but it mostly affected business sector. Social media is used in business sector, but during covid-19 pandemic situation social media is widely used in business sector for work effectively. The purpose of study is to determine the impact of social media on startup and growing business. The researcher wish to investigate how social Media influence on the growth of business and also to analyze which social media tools and application are used for effective work of business. Experiment were done on research data collected from the internet, Journal, Articles and personal prior knowledge. The result showed business sector are work or run effectively during pandemic situation. Most of business are used social media platform for example- Facebook, twitter, Instagram LinkedIn etc. Business sector are use social media platform for improving business both in quality and quantity. So, we conclude that, Business sector widely used social Media platform for effective and continuous work. This study is significant for Business Entrepreneur, Society, stakeholders, Government people and competitors.